Áreas protegidas no Pantanal de Mato Grosso : análise territorial no trecho do Rio Piquiri no Parque Estadual Encontro das Águas - Moraes, Elen da Silva (2013)
It is understood by the territory as the delimitation of a space for and from the relations marked by power. At a time when public and private interests merge driven by the need to move the market, the maintenance of open space and natural resources in common use, are at risk of permanence. These situations, generate discussions and actions by the government, which among other objectives, the option is to conserve biodiversity and natural resources. For that, we created protected areas, the vast majority on public lands, leading the transformation of spaces of common use, which is usually under pressure for use and occupation of the land. Among the protected areas, protected understood as territorial spaces that span numerous categories of legal protection and administrative constraints, may be cited the Conservation Units (CU). The Meeting of the Waters State Park (PEEA) was created in 2004 as compensation for legal reserve areas and covers the municipalities of Poconé and Barão de Melgaço, which aims to ensure the full protection of biotic and abiotic resources of the Pantanal region. UC is part of this river Piquiri space located on the border between the states of Mato Grosso and Mato Grosso do Sul. This study aims to identify, describe and analyze the existing territories in the stretch of the river Piquiri PEEA, as well as investigate activities and interests of various actors in the territory. The research method is the case study with a qualitative approach, using the following steps: definition of the unit case, data collection, selection, analysis and interpretation of data and reporting of the case. For this, we used the theoretical review from literature on the subject; institutional document analysis (gray literature); interviews; beyond the field research. The analyzes indicate the existence of four (04) disputed territories and conflicts in the river Piquiri, namely territory of conservation, professional fishing, the angling (fishing tourism), and watching tourism ounces. It is considered that even after the creation of PEEA , territories and stakeholders to continue to occupy this space , do so conflicting , pressures and threats characterizing the conservation of natural resources , especially in common use , such as resource fishing . You need to recognize and understand the relationships and social performance through a process of development of the area, noticeable paths to a more appreciative of maintaining the wetland environment.